The Influence of Work Motivation, Leadership Style, and Supervision on the Performance of Goods and Services Procurement Bureaucrats in the North Sulawesi Central Bureau of Statistics Work Unit - Remiasa, Simon; Masengi, Evi Elvira; Kairupan, Sisca (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The main objective of this study was to determine whether work motivation, leadership style, and supervision factors affect the performance of Goods and Services Procurement Bureaucrats in the Work Unit of the Central Bureau of Statistics in North Sulawesi. The problem encountered is that PBJ bureaucrats in the BPS work unit in North Sulawesi still violate the rules in terms of document fulfillment. The results of the research obtained there is a significant relationship between work motivation and employee performance in PBJ bureaucrats in BPS work units in North Sulawesi, there is a significant relationship between leadership style and employee performance in PBJ bureaucrats in BPS work units in North Sulawesi, and there is a significant relationship between supervision and employee performance in PBJ bureaucrats in BPS work units in North Sulawesi. Work motivation (X1), leadership style (X2), and supervision (X3) together contribute to the performance (Y) of PBJ bureaucrats in the BPS work unit in North Sulawesi. So it is concluded that work motivation, leadership style, and supervision affect the performance of Goods and Services Procurement Bureaucrats in the BPS work unit in North Sulawesi.